Entre triple contrainte et ancrage disciplinaire. Pratiques et conditions d'enseignement à l'Université - Romuald Bodin; Mathias Millet; Émilie Saunier (Les éditions de la Maison des sciences de l'Homme, 2018)
Drawing on primary data from a field survey - consisting of questionnaires (n=2273), interviews, and observations (n=90) - conducted in various French universities, this article aims at studying the status of teachers in higher education and its variations between academic disciplines, with a special focus on faculty members and other university teaching staff. It shows that the conditions in which they work carry with them important implications for the management of time and workload, with work often encroaching on the private and personal spheres of the individual, thereby causing a feeling of being overwhelmed. This article additionally reveals that, far from being antagonistic, teaching and research are mutually reinforcing activities, the former often constituting an important phase in intellectual work and production. In that regard, faculty members' reflections on teaching methods, tools, and devices also constitute a key factor in guiding their daily practices. Finally, this article sheds light on the specificities and variations of a professional career whose working and teaching activities differ from one research field to another; each field having its own understanding of "what knowing means."